Solve the following

Question:

Let $S_{1}=\sum_{j=1}^{10} j(j-1)^{10} C_{j}, S_{2}=\sum_{j=1}^{10} j^{10} C_{j}$ and $S_{3}=\sum_{j=1}^{10} j^{210} C_{j}$

Statement-1: $\mathrm{S}_{3}=55 \times 2^{9}$.

Statement-2 : $S_{1}=90 \times 2^{8}$ and $S_{2}=10 \times 2^{8}$.

  1. (1) Statement–1 is true, Statement–2 is true ; Statement–2 is a correct explanation for  Statement–1.

  2.  Statement–1 is true, Statement–2 is true ; Statement–2 is not a correct explanation for Statement–1.

  3.  Statement–1 is true, Statement–2 is false.

  4.  Statement–1 is false, Statement–2 is true.


Correct Option: , 3

Solution:

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now